Pityriasis Lichenoides et Varioliformis Acuta in Adult Woman with Asymptomatic Bacteriuria: Another Possible Trigger? - Theo Audi Yanto; Nathania Raphaeli Mulia; Abraham Fatah; Nana Novia Jayadi (Majalah Kedokteran Indonesia, 2023)
Introduction: Pityriasis Lichenoides et Varioliformis Acute (PLEVA) is a rare and benign inflammatory skin disease. This acute form is distinguished from the milder chronic condition, Pityriasis Lichenoides Chronica (PLC). The etiology of PLEVA itself remains unclear, although it has been associated with infection as a trigger.Case: Here, we present the case of a 34-year-old woman who presented with abrupt, generalized, pruritic skin eruptions for two months.Case Discussion: The eruptions started as red scaly papules and vesicles and resolved as hyperpigmentations. She denied having any previous dermatological diseases, routine medications, or vaccinations. On examination, she showed generalized multiple hyperpigmented macules, scaly papules, and vesicles over the trunk, extremities, and face, with erosions and crusts in several areas. Eosinophilia and asymptomatic bacteria were found in her urinalysis. A skin biopsy showed diffuse lymphocytic infiltration in the dermal/epidermal junction and perivascular region, with parakeratosis and lymphocyte exocytosis. While the pathogenesis of PLEVA itself remains unclear, a triggering factor of inflammatory reaction, such as infection, may contribute to the development of the disease.Conclusion: Asymptomatic bacteriuria is associated with inflammatory responses, and thus, it can be one of many possibilities. More studies are needed to confirm this association with PLEVA. Due to the lack of a clear pathogenesis and the benign nature of the disease, this rare entity may present difficulties in diagnosis and therapy